Pengembangan Sistem Pencatatan Pelanggaran Mahasiswa (Studi Kasus: Fakultas Ilmu Komputer Universitas Brawijaya) - Muhammad Rizqi Fauzi; Denny Sagita Rusdianto; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Discipline is important aspect in education. Sanctions can be educational tool to penalize student disciplinary. The unavailability of facilities to search for violators data and the accuracy of the data is in doubt. FILKOM of Brawijaya University have constraints filling record of student violation because history files student violation difficult to find. Based on the problem, author want to make application for help FILKOM managing history files student violation. The system development uses the waterfall Life Cycle Software (SDLC) waterfall with an object oriented approach. In the analysis phase, the authors applied the use case diagram and use case scenario. The design phase is done by creating sequence diagrams, class diagrams, entity relationship diagrams, and mocups. At the implementation stage, the authors use Laravel as a framework and MySQL as a database. After the implementation stage, application ready use with function can record violations of students with minor, moderate, severe violations and the application can also record book bills on violations that have a book fine. Testing on functional requirements uses unit testing and validation testing. The outcome shows 100% valid result on both tests. Testing for non-functional requirements uses browser compatibility testing. It shows that the system is compatible on Android, Chrome, Edge, Internet Explorer, Firefox, Opera, Safari and iPhone browsers.